Does supplementing β-mannanase modulate the feed-induced immune response and gastrointestinal ecology in poultry and pigs? An appraisal - Kiarie, Elijah G.; Steelman, Samantha; Martinez, Marco (Frontiers in Animal Science, 2022)
Provision of adequate and balanced nutrients is critical for efficient and profitable animal protein production. However, non-nutritive components in feedstuffs can elicit responses that can negatively impact nutrient utilization efficiency. For example, dietary β-mannans are recognizable by cell surface mannose receptors that are pivotal for various biological mechanisms such as immune response, adhesion, infection, and signal transduction. This review will evaluate physiological implications of dietary native β-mannans, utility of supplemental feed β-mannanase in hydrolyzing β-mannans and subsequent metabolic responses. Dietary native β-mannans have been implicated with inadvertent stimulation of immune response through a phenomenon coined feed-induced immune response (FIIR) that has been associated with intestinal inflammation and depression in animal performance. Supplemental β-mannanase blunted FIIR by hydrolyzing native β-mannans to smaller fragments with lower ability to stimulate innate immune as indicated by modulation of oxidative stress, mucosal permeability, and blood concentration of acute phase proteins and immunoglobulins in broilers and piglet models. Moreover, β-mannanase hydrolysis of native β-mannans to mannooligosaccharides (MOS) impacted gastrointestinal microbial ecology. Indeed, β-mannanase derived MOS reduced concentration of pathogenic bacteria such as E. coli, salmonella and increased lactic acid producing bacteria and short chain fatty acids in various animal models. Overall, β-mannans are not only anti-nutritive but elicit undesirable and metabolically costly immune responses; consequently, by hydrolyzing native β-mannans, supplemental β-mannanase may have nutritional, metabolic and microbial ecology benefits. In summary, integrating multi-functional feed additives such as β-mannanase in feeding programs for monogastric animals will be critical for efficient and sustainable animal protein production in the context of evolving issues such as the restriction on the use of antibiotics for growth promotion.